Escitalopram in the treatment of Malaysian patients with Obsessive-compulsive disorder - Hatim, A.; Gill, J.S.; Jambunathan, S.T.; Yen, T.H.; Ariff, M.; Lemming, O.M.; Azhar, M.Z. (2008)
Objective: This post-hoc analysis examined the efficacy and tolerability of escitalopram in the prevention of relapse in Malaysian patients with obsessive-compulsive disorder. Participants and Methods: In Malaysia, 47 patients with obsessive-compulsive disorder were treated with open-label escitalopram (10 mg or 20 mg/day) for 16 weeks, after which the 34 responders (Yale-Brown Obsessive Compulsive Scale total decrease score, 25) were randomised to placebo or escitalopram for 24 weeks, using a double-blind protocol. Results: The primary efficacy analysis suggested a trend in favour of escitalopram treatment with respect to time to relapse (log-rank test, p = 0.07). A higher proportion of patients relapsed after placebo treatment (5 of 14, 36) than with escitalopram treatment (2 of 20, 10) Fishers exact test, 2-sided; p = 0.10. The risk of relapse was 4-fold higher for placebo than escitalopram treatment (p = 0.09). During the double-blind period, the proportion of patients reporting treatment-emergent adverse events was comparable in the 2 groups (10% in the escitalopram group vs. 14% in the placebo group); no serious events being reported. Conclusions: This post-hoc subgroup analysis suggests that escitalopram is well tolerated in Malaysian patients with obsessive-compulsive disorder and appears to confer an advantage over placebo, in terms of time to relapse and other efficacy variables.